Busana Koko: Dinamika Kebudayaan Muslim dan Lifestyle Mahasiswa UIN Sunan Kalijaga - Nururi, Imam (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
This article discusses the intertwining of piety and lifestyle among students at the State Islamic University (UIN) Sunan Kalijaga Yogyakarta. This article focuses on the relationship between the use of koko clothes and the Islamic identity and lifestyle of UIN Sunan Kalijaga students. The purpose of this study is to find out how koko clothes, which are traditional Muslim men's clothes, experience interesting dynamics in the midst of campus culture that is rich in Islamic values which also become trending fashions for the wearers. The method used for literature analysis and ethnographic approach with the application of data collection techniques through observation and interviews is a process that involves analytical steps involving the initial stages of data collection, data reduction, data validation, and finally drawing conclusions. This research reveals that koko shirts for students have more meaning than just fashion. Through literature analysis and an ethnographic approach, baju koko is identified as a profound expression of students' personal identity and values. The findings highlight that the choice of baju koko is not just a style of dress, but also a powerful symbol in shaping one's self-concept and cultural identity.